Stratospheric downward wave reflection events modulate North American weather regimes and cold spells - G. Messori; G. Messori; G. Messori; G. Messori; M. Kretschmer; S. H. Lee; V. Wendt; V. Wendt (Weather and Climate Dynamics, 2022)
The Arctic stratospheric polar vortex is an important driver of mid-latitude winter cold spells. One proposed coupling mechanism between the stratospheric polar vortex and the troposphere is upward-propagating planetary waves being reflected downward by the polar vortex. However, while the wave reflection mechanism is well-documented, its role in favouring cold spells is still under-explored. Here, we analyse such stratospheric wave reflections and their impact on the tropospheric circulation and surface temperatures over North America in winter. We present a physically interpretable regional stratospheric wave reflection detection metric and identify the tropospheric circulation anomalies associated with prolonged periods of wave reflection, which we term reflection events. In particular, we characterise the tropospheric anomalies through the lens of North American weather regimes. Stratospheric reflection events show a systematic evolution from a Pacific Trough regime – associated on average with positive temperature anomalies and a near-complete absence of anomalously cold temperatures in North America – to an Alaskan Ridge regime, which favours low temperatures over much of the continent. The most striking feature of the stratospheric reflection events is thus a rapid, continental-scale decrease in temperatures. These emerge as continental-scale cold spells by the end of the reflection events. Stratospheric reflection events are thus highly relevant in a tropospheric predictability perspective.